Does working capital management influence operating and market risk of firms? - Ahsan Akbar; Minhas Akbar; Marina Nazir; Petra Poulova; Samrat Ray (Risks, 2021)
Extant empirical studies have predominantly focused on the nexus between working capital management (WCM) and corporate profitability. While there is a dearth of literature on the nexus between WCM and a firm's risk, the present study examines Pakistani-listed firms coming from 12 diverse industrial segments to observe this association for a time span of ten years (2005-2014). To ensure robustness, we employed a System Generalized Method of Moments (SGMM) regression estimation to investigate the influence of WCM on the operational and market risk for firms. Empirical testing revealed that higher working capital levels were associated with lower volatility in firms' stock price, which shows that shareholders prefer a conservative working capital policy. Moreover, firms with better cash positions were subject to lesser stock market volatility. In contrast, excess working capital and a larger net trade cycle were associated with increased volatility in the operating income. Besides, firms with lower working capital levels relative to their respective industry experienced fewer fluctuations in their operating profits. Our findings assert that short-term financial management has important ramifications for firms' operating and market fundamentals. Practical implications are discussed for corporate managers and relevant stakeholders.
Keywords: 330; working capital management; operating risk; market risk; system gmm; listed firms; Pakistan